2021
DOI: 10.1093/nutrit/nuaa115
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding tendency and ascorbic acid requirements: systematic review and meta-analysis of clinical trials

Abstract: Context The World Health Organization set the recommended daily vitamin C intake, henceforth referred to as ascorbic acid (AA), on the basis of scurvy prevention. Double-blind AA depletion-repletion studies suggest that this recommended AA dose may be too low to prevent microvascular fragility. Objectives (1) To conduct a systematic review and meta-analysis of controlled clinical trials on whether AA supplementation leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…The other enzymes for which vitamin C acts as a cofactor are involved in carnitine synthesis, catecholamine synthesis, peptide amidation, and tyrosine metabolism [28]. Due to its essential role in collagen biosynthesis, deficiency of vitamin C compromises the integrity of blood vessels, leading to scorbutic gums and pinpoint hemorrhage, characteristic manifestations of vitamin C deficiency [32].…”
Section: As a Cofactor For Conventional Enzymesmentioning
confidence: 99%
“…The other enzymes for which vitamin C acts as a cofactor are involved in carnitine synthesis, catecholamine synthesis, peptide amidation, and tyrosine metabolism [28]. Due to its essential role in collagen biosynthesis, deficiency of vitamin C compromises the integrity of blood vessels, leading to scorbutic gums and pinpoint hemorrhage, characteristic manifestations of vitamin C deficiency [32].…”
Section: As a Cofactor For Conventional Enzymesmentioning
confidence: 99%
“…The National Academy of Medicine described an increased gingival bleeding tendency as one of the most sensitive markers for a vitamin C deficiency in 2000 [95]. Clinical trials focusing on bleeding tendency confirmed these conclusions [96]. Nevertheless, the conventional wisdom is to largely ignore a vitamin C deficiency in the etiology of gingival bleeding.…”
Section: A Preponderance Of Clinical Trial Evidence Becomes Heresymentioning
confidence: 99%
“…This aim seems as unrealistic as uncausal, as proven by the discrepancy between the already high level of oral hygiene efforts of industrialized populations and the still remaining high prevalence of oral diseases. Furthermore, if the causes of these diseases may lie in other factors than plaque, plaque control would accordingly only be a symptomatic approach that would blur the symptoms but not the underlying causal factor [ 21 , 22 ]. This implies at least two harmful or detrimental consequences for personal and even public health care: the primary bodily “warning signal” in the form of gingivitis, e.g., as a consequence of excessive sugar consumption or micronutrient deficiency, would not lead to a cause-related therapy (sugar cessation or supply of micronutrients) but to a symptomatic plaque reduction [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, if the causes of these diseases may lie in other factors than plaque, plaque control would accordingly only be a symptomatic approach that would blur the symptoms but not the underlying causal factor [ 21 , 22 ]. This implies at least two harmful or detrimental consequences for personal and even public health care: the primary bodily “warning signal” in the form of gingivitis, e.g., as a consequence of excessive sugar consumption or micronutrient deficiency, would not lead to a cause-related therapy (sugar cessation or supply of micronutrients) but to a symptomatic plaque reduction [ 21 , 22 , 23 ]. While the gingivitis would get better, the malnutrition would not and may lead to further diseases (e.g., overweight or retinal hemorrhaging).…”
Section: Introductionmentioning
confidence: 99%